2021
DOI: 10.1523/jneurosci.1392-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Lunatic Fringe-GFP Marks Lamina-Specific Astrocytes That Regulate Sensory Processing

Abstract: Astrocytes are the most abundant glial cell in the brain and perform a wide range of tasks that support neuronal function and circuit activities. There is emerging evidence that astrocytes exhibit molecular and cellular heterogeneity; however, whether distinct subpopulations perform these diverse roles remains poorly defined. Here we show that the Lunatic Fringe-GFP (Lfng-GFP) bacteria artificial chromosome mouse line from both sexes specifically labels astrocyte populations within lamina III and IV of the dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…There is renewed interest in understanding astrocyte biology in health and disease, necessitating the exploration of astrocytes with high-dimensional molecular data in different regions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). By comparing astrocytes across 13 CNS regions, we found ~850 genes that were shared, with functions related to metabolism, cholesterol biosynthesis, and neurotransmitter uptake and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is renewed interest in understanding astrocyte biology in health and disease, necessitating the exploration of astrocytes with high-dimensional molecular data in different regions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). By comparing astrocytes across 13 CNS regions, we found ~850 genes that were shared, with functions related to metabolism, cholesterol biosynthesis, and neurotransmitter uptake and biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike neurons, which are extremely diverse within neural circuits, astrocytes have traditionally been viewed as being homogeneous. However, recent gene expression and functional studies using different methods in the context of health and brain tumors have shown that astrocytes are separable between several central nervous system (CNS) regions (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). This has led to the realization that astrocytes may be diverse, an attribute that, together with their highly complex morphology, may allow them to mediate their multiple roles in different parts of the CNS.…”
mentioning
confidence: 99%
“…[35][36][37] These tools permit an interrogation of the gene networks that distinguish astrocyte subgroups, as well as the identification of genetic markers for labeling and manipulating specific astrocyte subgroups. [38][39][40] Recent work highlights the diversity of astrocytes across different brain regions (inter-regional heterogeneity) and within regions of the brain (intra-regional heterogeneity). 9,41 These populations exhibit distinct molecular, morphological, and physiological features that likely reflect their region-specific functional roles.…”
Section: Inter-regional Diversity Of Astrocytesmentioning
confidence: 99%
“…The recent identification of astrocyte-expressing genes by transcriptome analyses suggests that astrocytes display inter- or intra-regional heterogeneity and act as a gate for descending noradrenergic control of mechanosensory behavior, which indicates the diverse functions and phenotypes of astrocytes for chronic pain regulation [ 169 ]. Akdemir et al also found that subpopulations of Lfng-labeled astrocytes in laminae III and IV of the dorsal horn are involved in the regulation of neuronal activity and maintaining sensory-processing circuity associated with light touch [ 170 ]. Ablation of Lfng+ astrocytes reduces glutamatergic synapses and mechanosensory responses.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%